Hemodynamic and anatomic changes after fetal aortic valvuloplasty are associated with procedural success and postnatal biventricular circulation. (19th August 2022) - Bradford, Victoria R.; Tworetzky, Wayne; Callahan, Ryan; Wilkins‐Haug, Louise E.; Benson, Carol B.; Porras, Diego; Guseh, Stephanie H.; Lu, Minmin; Sleeper, Lynn A.; Gellis, Laura; Friedman, Kevin G.
Abstract: Background: There are minimal data characterizing the trajectory of left heart growth and hemodynamics following fetal aortic valvuloplasty (FAV). Methods: This retrospective study included patients who underwent FAV between 2000 and 2019, with echocardiograms performed pre‐FAV, immediately post‐FAV, and in late gestation. Results: Of 118 fetuses undergoing FAV, 106 (90%) underwent technically successful FAV, of which 55 (52%) had biventricular circulation. Technically successful FAV was associated with improved aortic valve growth ( p < 0.001), sustained antegrade aortic arch (AoA) flow ( p = 0.02), improved mitral valve (MV) inflow pattern ( p = 0.002), and favorable patent foramen ovale (PFO) flow pattern ( p = 0.004) from pre‐FAV to late gestation. Compared to patients with univentricular outcome, patients with biventricular outcome had less decrement in size of the left ventricle (LV) ( p < 0.001) and aortic valve ( p = 0.005), as well as more physiologic PFO flow ( p < 0.001) and antegrade AoA flow ( p < 0.001) from pre‐FAV to late gestation. In multivariable analysis, echocardiographic predictors of biventricular outcome were less decline in LV end diastolic dimension ( p < 0.001), improved PFO flow ( p = 0.004), and sustained antegrade AoA flow ( p = 0.002) from pre‐FAV to late gestation. Conclusion: Stabilization of left heart growth and improved hemodynamics following successful FAV through late gestation are associated with postnatal biventricular circulation. Key points: What's already known about this topic? Fetal aortic valvuloplasty (FAV) may prevent the progression of severe fetal aortic stenosis (AS) to hypoplastic left heart syndrome (HLHS) at birth. Fetal predictors of postnatal circulatory outcomes at discrete time points during gestation have been previously identified. What does this study add? Technically successful FAV is associated with improved aortic valve growth trajectory and sustained improvement in hemodynamic parameters from pre‐FAV through late gestation. In patients with technically successful FAV, improved left heart growth trajectory, sustained antegrade aortic arch (AoA) flow, and improved patent foramen ovale (PFO) flow following FAV are associated with higher odds of postnatal biventricular circulation.